Moderation of Dow Jones Industrial Average in the Dynamics of Indonesian Sharia Stock Index: Global Sharia Index and Macroeconomic Review - R, Abdul Azis (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This research seeks to examine the impact of the Global Islamic Stock Index (Dow Jones Islamic Market US) and macroeconomic factors (Inflation, BI Rate, Exchange Rate, and Money Supply) on the Indonesian Sharia Stock Index, with the Dow Jones Industrial Average (DJIA) acting as a moderating variable. Employing a quantitative methodology, the study incorporates descriptive analysis and hypothesis testing using the SmartPLS application to assess estimation outcomes. Secondary data from 2014 to 2023, including monthly Inflation, BI Rate, Exchange Rate, and Money Supply figures, taken from the official website of Bank Indonesia. Data for ISSI, DJIMUS, and DJIA were obtained from monthly closing prices on www.finance.yahoo.com. Findings reveal that DJIMUS exerts a significant negative influence on ISSI, while DJIA does not significantly moderate this relationship. Inflation and the BI Rate show no significant effects on ISSI; however, DJIA significantly moderates the BI Rate's influence on ISSI. The Exchange Rate has a significant negative impact on ISSI, whereas the Money Supply demonstrates a significant positive effect, though DJIA does not moderate its influence. The study focuses on monthly data from 2014 to 2023, limiting its reflection of daily or weekly stock market fluctuations. This research offers insights for academics and practitioners in Islamic finance and macroeconomics by exploring the interplay between global Islamic stock indices, macroeconomic indicators, and domestic Islamic stock indices, with consideration of global stock market moderation